Cataract Surgery in Elderly Patients: Impact on Life Quality and Functionality - Armando Rafael Milanés Armengol; Kattia Molina Castellanos; Inés Zamora Galindo; Alina González Díaz; Jorge Jackson Villalpando Rodríguez; Yisel María Mayo Saavedra (Medisur)
Background: cataract surgery becomes highly valuable in our days because it acts on one of the leading causes of preventable blindness. Objective: To assess the impact of cataract surgery on the functionality and life quality of the elderly. Methods: case series study of all elderly patients who attended Ophthalmology Consultation at the Integral Diagnostic Center Mesones in Bolivar, Anzoategui State, Venezuela, from February to November 2007 for cataract surgery and who met the inclusion criteria. A survey and a set of assessment tools were applied in order to measure: functional status, siymptoms score and visual VF-14 function index which provided an assessment of life quality in two stages: in the preoperative stage and three months after surgery, thus allowing restoration of the various functions after surgery. Results: There was a significant improvement in visual acuity represented by a visual recovery of a 92%; according VF-14 index of visual function, life quality improved in a 92 %; general validism was recovered in 482 patients and 57 of them are considered to depend on other people for only one activity of their daily living, 6.1% of patients still present symptoms related to symptom score. Conclusions: patients who underwent cataract surgery showed evidence of improvement in visual acuity, functionality and life quality.